Microfabrication of Self-assembled Systems: Design and Optimisation of Self-assembled Nanocomposites for Direct Laser Writing - Augustine, Amrutha (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
The addition of nanofillers into polymer matrices can endow added functionality to the polymer nanocomposite, such as enhanced conductive, magnetic, optical and mechanical properties, among others. In this Thesis, we demonstrate the development of novel nanocomposite photoresists suitable for direct laser writing via two photon polymerisation (DLW-2PP).
APPROVED
Keywords: Direct Laser Writing; Two Photon Polymerisation; Silica nanoparticles; Cellulose nanocrystals; Nanocomposite photoresists for DLW-2PP